2015
DOI: 10.31843/jmbi.v3i1.75
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepuasan Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan/ti Dengan Komitmen Organisasional Sebagai Variabel Intervening (Studi Karyawan Outsourcing PT. J Yang Ditempatkan Di Kampus II Untar Jakarta).

Abstract: This study on the Influence Job Satisfaction and Job Motivation on Employee Performance with Organizational Commitment as an Intervening Variable (Study of Employee outsourcing PT J placed Tarumanagara University. Population in this study all employees outsourcing PT J, with sampling techniques is purposive random sampling, and samples taken 50 employees. Purpose of the study is to examine and analyze the effect of job satisfaction and motivation on employee performance. Analysis is the method of multiple regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
1
0
6
Order By: Relevance
“…The level of employee commitment to the organization can also be influenced by work motivation and job satisfaction. Based on research from Nawawi (2015) Mathieu et al (2016), revealed that job satisfaction influences organizational commitment so that it means that higher work motivation and job satisfaction, the higher employee commitment to the organization. If nurses have a high organizational commitment, then indirectly, they can also reduce turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…The level of employee commitment to the organization can also be influenced by work motivation and job satisfaction. Based on research from Nawawi (2015) Mathieu et al (2016), revealed that job satisfaction influences organizational commitment so that it means that higher work motivation and job satisfaction, the higher employee commitment to the organization. If nurses have a high organizational commitment, then indirectly, they can also reduce turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Nawawi (2015) menyatakan bahwa kepuasan kerja merupakan faktor penting dalam mempengaruhi kepuasan hidup manusia karena sebagian besar waktu dihabiskan di tempat mereka bekerja. Sedangkan menurut Ellys & Ie (2020), kepuasan kerja merupakan perasaan senang atau kecewa karyawan terhadap pekerjaan dan perusahaan tempat mereka bekerja.…”
Section: Kajian Teori Kepuasan Kerjaunclassified
“…Dalam penelitian yang dilakukan oleh Okwudili dan Ogbu, (2017) telah membuktikan bahwa kompensasi langsung dan tidak langsung, akan meningkatkan kinerja karyawan, dengan hasil yang menyatakan bahwa kompensasi berpengaruh signifikan terhadap kinerja karyawan. sedangkan penelitian lain yang dilakukan oleh (Nawawi, 2015;Olusadum dan Anulika, 2018;Nikensari et al, 2018) membuktikan bahwa motivasi kerja memiliki dampak yang signifikan terhadap kinerja karyawan.…”
Section: Kajian Teoriunclassified
“…Beberapa hasil studi juga membuktikan bahwa kepuasan kerja berpengaruh signifikan terhadap kinerja karyawan (Inuwa, 2016;Panchal, 2016;Nawawi, 2015).…”
Section: Kajian Teoriunclassified